Move <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mo>-</mo><mn>3</mn></mrow></msup></mstyle></math> to the denominator using the negative exponent rule <math><mstyle displaystyle="true"><msup><mrow><mi>b</mi></mrow><mrow><mo>-</mo><mi>n</mi></mrow></msup><mo>=</mo><mfrac><mrow><mn>1</mn></mrow><mrow><msup><mrow><mi>b</mi></mrow><mrow><mi>n</mi></mrow></msup></mrow></mfrac></mstyle></math> .

Move <math><mstyle displaystyle="true"><msup><mrow><mi>z</mi></mrow><mrow><mo>-</mo><mn>2</mn></mrow></msup></mstyle></math> to the denominator using the negative exponent rule <math><mstyle displaystyle="true"><msup><mrow><mi>b</mi></mrow><mrow><mo>-</mo><mi>n</mi></mrow></msup><mo>=</mo><mfrac><mrow><mn>1</mn></mrow><mrow><msup><mrow><mi>b</mi></mrow><mrow><mi>n</mi></mrow></msup></mrow></mfrac></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> by <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> by adding the exponents.

Move <math><mstyle displaystyle="true"><msup><mrow><mi>y</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> .

Use the power rule <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi></mrow></msup><msup><mrow><mi>a</mi></mrow><mrow><mi>n</mi></mrow></msup><mo>=</mo><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi><mo>+</mo><mi>n</mi></mrow></msup></mstyle></math> to combine exponents.

Add <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><msup><mrow><mi>z</mi></mrow><mrow><mn>5</mn></mrow></msup></mstyle></math> by <math><mstyle displaystyle="true"><msup><mrow><mi>z</mi></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> by adding the exponents.

Move <math><mstyle displaystyle="true"><msup><mrow><mi>z</mi></mrow><mrow><mn>2</mn></mrow></msup></mstyle></math> .

Use the power rule <math><mstyle displaystyle="true"><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi></mrow></msup><msup><mrow><mi>a</mi></mrow><mrow><mi>n</mi></mrow></msup><mo>=</mo><msup><mrow><mi>a</mi></mrow><mrow><mi>m</mi><mo>+</mo><mi>n</mi></mrow></msup></mstyle></math> to combine exponents.

Add <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>5</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>9</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>5</mn></mrow></msup></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup><msup><mrow><mi>y</mi></mrow><mrow><mn>6</mn></mrow></msup><msup><mrow><mi>z</mi></mrow><mrow><mn>7</mn></mrow></msup></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Factor <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> out of <math><mstyle displaystyle="true"><mn>3</mn><msup><mrow><mi>x</mi></mrow><mrow><mn>5</mn></mrow></msup></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup></mstyle></math> out of <math><mstyle displaystyle="true"><msup><mrow><mi>x</mi></mrow><mrow><mn>3</mn></mrow></msup><msup><mrow><mi>y</mi></mrow><mrow><mn>6</mn></mrow></msup><msup><mrow><mi>z</mi></mrow><mrow><mn>7</mn></mrow></msup></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Do you know how to Simplify (9x^5y^-3z^-2)/(3x^3y^3z^5)? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.